Opening the Strands of Replication Origins—Still an Open Question - Jha, Jyoti K.; Ramachandran, Revathy; Chattoraj, Dhruba K. (Frontiers in Molecular Biosciences, 2016)
The local separation of duplex DNA strands (strand opening) is necessary for initiating basic transactions on DNA such as transcription, replication and homologous recombination. Strand opening is commonly a stage at which these processes are regulated. Many different mechanisms are used to open the DNA duplex, the details of which are of great current interest. In this review, we focus on a few well-studied cases of DNA replication origin opening in bacteria. In particular, we discuss the opening of origins that support the theta () mode of replication, which is used by all chromosomal origins and many extra-chromosomal elements such as plasmids and phages. Although the details of opening can vary among different origins, a common theme is binding of the initiator to multiple sites at the origin, causing stress that opens an adjacent and intrinsically unstable A+T rich region. The initiator stabilizes the opening by capturing one of the open strands. How the initiator binding energy is harnessed for strand opening remains to be understood.